Efforts To Improve Employee Performance Through Incentives, Work Skills, And Intrinsic Motivation, With Organizational Commitment As An Intervening Variable : Study Of CV. Mita Furniture Jepara Employees - Ahmad Fahmi Fahrobi; Suparjo Suparjo; Sulistiyani Sulistiyani (Proceeding of The International Conference on Economics and Business, 2022)
This study aims to analyze the effect of incentives, work skills, and intrinsic motivation on employee performance either directly or indirectly through organizational commitment on CV. Mita Funiture Jepara. The population used in this study were all employees of CV Mita Furniture Jepara, and the number of samples used was 83 respondents, with the sampling technique of the saturated sample method or the census method. The data source used is primary data, with questionnaire data collection method. The analytical technique used is path analysis and Sobel test. The results of the research analysis show that incentives have a positive and significant effect on organizational commitment, work skills have a positive and significant effect on organizational commitment, intrinsic motivation has a positive and significant effect on organizational commitment, incentives have a positive and significant effect on employee performance, work skills have a positive and significant effect on organizational commitment. employee performance, intrinsic motivation has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance. Sobel test results show that organizational commitment can mediate or strengthen the effect of incentives on employee performance, organizational commitment can mediate or strengthen the effect of work skills on employee performance, and organizational commitment can mediate or strengthen the effect of intrinsic motivation on employee performance.